Efektivitas Model Problem Based Learning Dalam Meningkatkan Kemapuan Pemecahan Masalah Matematis Pada Siswa Sekolah Dasar - Safira, Denta (Didaktika, 2022)
The learning model serves as  a guide for learning designers and teachers in planning teaching and learning activities. Problem-Based Learning model provides students to think about a problem and then the problem is solved using the correct solution. The purpose of this study was to determine the effectiveness of the Problem-Based Learning model and student responses to the use of the Problem-Based Learning model in elementary schools. Thus it can help students to optimize problem solving skills in students. This study uses an experimental method with Matching pre-test post-test Control Group Design. The samples were taken from the entire class population of 40 students from 4th grade at the State of Elementary School of Buah Gede. The test instrument used in the form of questions and non-test instrument in the form of a questionnaire. Analysis of the collected data were analyzed by normality and homogeneity tests as a prerequisite test for the experimental group and the control group. Problem-Based Learning model is effective to be used in improving students' mathematical problem solving and student responses give good responses to the use of Problem-Based Learning model. Teachers are expected to utilise appropriate learning methods for mathematical problem solving and similar problems.